Adaptation of the crystal structure to the confined size of mixed-oxide nanoparticles - Makovec, Darko (Acta chimica slovenica, 2022)
Chemical composition and crystal structure are central to defining the functional properties of materials. But when a material is prepared in the form of nanoparticles, the structure and, as a consequence, the composition will also frequently change. Understanding these changes in the crystal structure at the nanoscale is therefore essential not only for expanding fundamental knowledge, but also for designing novel nanostructures for diverse technological and medical applications. The changes can originate from two thermodynamically driven phenomena: (i) a crystal structure will adapt to the restricted size of the nanoparticles, and (ii) metastable structural polymorphs that form during the synthesis due to a lower nucleation barrier (compared to the equilibrium phase) can be stabilized at the nanoscale. The changes to the crystal structure at the nanoscale are especially pronounced for inorganic materials with a complex structure and composition, such as mixed oxides with a structure built from alternating layers of several structural blocks. In this article the complex structure of nanoparticles will be presented based on two examples of well-known and technologically important materials with layered structures: magnetic hexaferrites (BaFe12O19 and SrFe12O19) and ferroelectric Aurivillius layered-perovskite bismuth titanate (Bi4Ti3O12).
Keywords: Aurivillius structure; crystal structure; hexaferrites; kristalna struktura; layered perovskites; Nanodelci; nanoparticles; Perovskit; Polimorfizem (kristalografija); polymorphisms